Sorafenib-Associated Heart Failure Complicated by Cardiogenic Shock after Treatment of Advanced Stage Hepatocellular Carcinoma: A Clinical Case Discussion - Candace Wu; Kamal Shemisa (Case Reports in Cardiology)
Background. Sorafenib, an oral tyrosine kinase inhibitor (TKI), targets multiple tyrosine kinase receptors (TKRs) involved in angiogenesis and tumor growth. Studies suggest that inhibition of TKR impacts cardiomyocyte survival. Inhibition of VEGF signaling interrupts angiogenesis and is associated with the development of hypertension and compensatory hypertrophy. Compensated hypertrophy ultimately leads to heart failure. Case Description. A 76-year-old man with a past medical history of systolic heart failure due to ischemic cardiomyopathy and stage IIIC hepatocellular carcinoma (HCC) presented with symptoms of decompensated heart failure. Four months prior to admission, he was started on sorafenib. Results. Our patient was treated with intravenous furosemide and guideline directed therapy. Clinical status was complicated by the development of low cardiac output and shock requiring inotropic support. Careful titration of heart failure medication led to hemodynamic improvement and discontinuation of dobutamine. Conclusion. Greater awareness of sorafenib cardiotoxicity is essential. As TKI usage grows for treatment of cancers, heart failure-related complications will increase. In our patient, routine heart failure management and cessation of sorafenib led to clinical improvement. Future studies on the treatment of sorafenib cardiotoxicity should be explored further in this unique patient population.